Allergic rhinitis, asthma and atopic diseases: Bangladesh perspective (Bangladesh Journal of Otorhinolaryngology, 2009)
Bangladesh is a developing country with 150 million population. About 20 to 25% of population is suffering from different types of allergic disorder. Few studies were carried out on asthma, allergic rhinitis and atopic conditions in Bangladesh. There are many indoor, outdoor, occupational and food allergens that trigger allergy. More over many pollutants, allergens are still unidentified in the poor and developing countries due to fund constrains for research activities. In addition to multiple known and unknown allergens, over population, un-hygienic living, poverty, lack of education and awareness, negligence to take treatment leads to increasing incidence of these diseases. Diagnostic facilities are yet depending on history and clinical examination for majority of our patients. Skin prick tests and IgE estimation are not available outside capital Dhaka as well as these are expensive too. Majority of our population can't afford them. Asthma and allergies are affecting the quality of life that has impact on national economy and development a lot. Treatment modalities and drugs available with the costs in our country are discussed. More evidence based studies and dissemination of ARIA, WHO and other guidelines to health professionals will be needed to improve the situation. Key words: Asthma, Allergic Rhinitis, Atopic DermatitisDOI: 10.3329/bjo.v14i2.3284 Bangladesh J of Otorhinolaryngology 2008; 14(2) : 66-70